HUBUNGAN ANTARA DUKUNGAN SOSIAL ORANG TUA DAN PRESTASI BELAJAR IPA SISWA KELAS V SDN 13 BIRU WATAMPONE - Sudarto Sudarto; Muliadi Muliadi; Firawati Firawati (STKIP Subang, 2023)
The problem in this study is the lack of parental social support that students get. Parents are still lacking in giving time to guide, motivate, and provide full learning support for students. This research is a quantitative research with a correlational design that aims to determine the correlation between parental social support and science learning achievement of fifth grade students. The results showed that there was a significant correlation between parental social support and science learning achievement for fifth grade students with tcount (3.3164) greater (˃) ttable value (1.67722), which means H0 is rejected and H1 is accepted. Based on the analysis of the data above, it can be concluded that parental social support has an impact on students' science learning achievement. So, the better the social support of parents, the better the student's science learning achievement. From these conclusions, the impact resulting from this study is known that good parental social support will increase students' science learning achievement.